Design and Performance Optimization in Wireless Power Transfer System - S., Vasantharathna; I., Paul Samuel; A., Arun; R., Balamurugan; R., Bharath (Journal of Electronics and Informatics, 2025)
Wireless Power Transfer (WPT) is one of the contactless energy transmission technologies that does not require physical connectors, and it improves efficiency in various applications such as electric vehicles, consumer electronics, and medical devices. In this article, the issue of optimizing the design and performance of an inductive WPT system based on LCC compensation has been proposed for better power transfer efficiency. The system topology consists of a high-frequency H-bridge inverter, coupling coils, and an AC-DC stage for efficient energy transfer. The LCC compensation network used in the system will reduce the impedance mismatch and maximize the coupling coefficient for improving transmission efficiency with larger air gaps. The simulation results correlate with the theoretical model. The proposed design shows an effective result. Thus, the optimized WPT system provides an energy transfer efficiency of 81.7%, affirming its feasibility for sustainable and high-performance applications.